2012
DOI: 10.1042/bj20111887
|View full text |Cite
|
Sign up to set email alerts
|

A new validated mathematical model of the Wnt signalling pathway predicts effective combinational therapy by sFRP and Dkk

Abstract: The Wnt signalling pathway controls cell proliferation and differentiation, and its deregulation is implicated in different diseases including cancer. Learning how to manipulate this pathway could substantially contribute to the development of therapies. We developed a mathematical model describing the initial sequence of events in the Wnt pathway, from ligand binding to β-catenin accumulation, and the effects of inhibitors, such as sFRPs (secreted Frizzled-related proteins) and Dkk (Dickkopf). Model parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 45 publications
4
62
0
1
Order By: Relevance
“…Until now, increasing evidences have demonstrated that multiple negative modulators could antagonize Wnt/β-catenin signaling through recruiting different mechanisms. For example, secreted Frizzled-related proteins (SFRPs) and Wnt inhibitory factor-1 (WIF-1) are able to directly bind Wnt proteins and block Wnt/ β-catenin pathway, and Dickkopf1 (DKK1) negatively regulates Wnt signaling via interacting with Wnt co-receptors LRP5/LRP6 whereas GSK3β displays its suppression on Wnt/β-catenin pathway through phosphorylating β-catenin, leads to the proteasome proteolytic degradation of β-catenin [28, 33, 34]. Moreover, nuclear transcriptionalsuppressors including transducin-like enhancer of split 3 (TLE3) inhibit the transcriptional activity of LEF/TCF [35].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, increasing evidences have demonstrated that multiple negative modulators could antagonize Wnt/β-catenin signaling through recruiting different mechanisms. For example, secreted Frizzled-related proteins (SFRPs) and Wnt inhibitory factor-1 (WIF-1) are able to directly bind Wnt proteins and block Wnt/ β-catenin pathway, and Dickkopf1 (DKK1) negatively regulates Wnt signaling via interacting with Wnt co-receptors LRP5/LRP6 whereas GSK3β displays its suppression on Wnt/β-catenin pathway through phosphorylating β-catenin, leads to the proteasome proteolytic degradation of β-catenin [28, 33, 34]. Moreover, nuclear transcriptionalsuppressors including transducin-like enhancer of split 3 (TLE3) inhibit the transcriptional activity of LEF/TCF [35].…”
Section: Discussionmentioning
confidence: 99%
“…Antagonists of Wnt signaling include secreted Frizzled-related protein (sFRP), Wnt inhibitory factor 1 (WIF-1), and Dickkopf (Dkk). Mathematical models have been used to investigate the effect of inhibiting Wnt via its antagonists and, in one example, modeling was applied to investigate Wnt inhibition via Wnt3a, sFRP, and Dkk [74]. The effect of inhibiting Wnt signaling was quantified by estimating the accumulation of β-catenin, which leads to the transcription of various genes involved in EC proliferation, migration, and other processes.…”
Section: Computational Models Of Anti-angiogenic Therapeuticsmentioning
confidence: 99%
“…Additionally, the model simulated the effect of Dkk alone and in combination with sFRP. Interestingly, Dkk and sFRP were predicted to have a synergistic effect on inhibiting β-catenin accumulation [74], and this work could lead to a new anti-angiogenic treatment strategy.…”
Section: Computational Models Of Anti-angiogenic Therapeuticsmentioning
confidence: 99%
“…Computational methods have been developed for predicting drug combination effects from gene expression profiles of drug-treated samples1112131415 and simulation of drug-targeted signaling161718192021 and metabolic22232425 pathways. In particular, simulation of drug-targeted pathways is potentially useful for predicting CIs1726, as demonstrated by the successful applications of the chemogenomic profile based models2728 and the statistically-inferenced network models2930 for the prediction of synergistic effects of drug combinations.…”
mentioning
confidence: 99%
“…These also provide useful knowledge for developing drug or drug combination targeted mathematical models for a number of pathways targeted by drugs and drug combinations (e.g. EGFR-ERK3132333435, apoptosis3637, NFκB1617, Wnt19 and disease-relevant metabolic22232425 pathways).…”
mentioning
confidence: 99%